Evaluation of prescribing pattern of NSAIDs in south Indian teaching hospital - Kumar, S; Thakur, P K; Sowmya, K; Priyanka, S (Journal of Chitwan Medical College, 2017)
The present study was aimed to appropriateness of NSAIDs use with secondary objectives of assessment of co-prescription with gastro-protective agents, the nature and severity of adverse drug reactions and drug-drug interactions with an intention to prevent the inappropriate use of NSAIDs. A prospective study was carried out in 400 In-patients of various departments of the hospital during the 6 months period. Results: Out of 400 patients, 237 were male and 163 were females, in which most of the patients (63.5%) were belonging to age group of 21-50years. The major complaint of the patient was arthritic pain (25.5%). Most of the patients (77%) were prescribed single NSAID as monotherapy in different dosage forms, although some patients were prescribed with combination of Aceclofenac + Paracetamol (13.75%). The preferential COX-2 inhibitors were widely prescribed (84.5%) as compared to non-selective COX inhibitor (15.5%). Among various NSAIDs prescribed, Diclofenac (45.90%) and Aceclofenac (15.96%) were mostly prescribed. NSAIDs were mostly prescribed by parenteral route (36.31%). Most of the patients were co-prescribed NSAIDs with gastro-protective agents (80.5%). In the study, moderate drug interactions were found between NSAIDs and antibiotics and no adverse drug reactions were reported during the study. The study concluded that, prescription of NSAIDs was found to be rational. Education program, counselling program, alertness of community pharmacy regarding OTC drugs can be helpful to minimize harmful effect of the drug to patients.